Focusing on variation: methods and applications of the concept of beta diversity in aquatic ecosystems Focando na variação: métodos e aplicações do conceito de diversidade beta em ecossistemas aquáticos - Adriano Sanches Melo; Fabiana Schneck; Luiz Ubiratan Hepp; Nadson Ressyé Simões; Tadeu Siqueira; Luis Mauricio Bini (Acta Limnologica Brasiliensia, 2011)
Ecologists usually estimate means, but devote much less attention to variation. The study of variation is a key aspect to understand natural systems and to make predictions regarding them. In community ecology, most studies focus on local species diversity (alpha diversity), but only in recent decades have ecologists devoted proper attention to variation in community composition among sites (beta diversity). This is in spite of the fact that the first attempts to estimate beta diversity date back to the pioneering work by Koch and Whittaker in the 1950s. Progress in the last decade has been made in the development both of methods and of hypotheses about the origin and maintenance of variation in community composition. For instance, methods are available to partition total diversity in a region (gamma diversity), in a local component (alpha), and several beta diversities, each corresponding to one scale in a hierarchy. The popularization of the so-called raw-data approach (based on partial constrained ordination techniques) and the distance-based approach (based on correlation of dissimilarity/distance matrices) have allowed many ecologists to address current hypotheses about beta diversity patterns. Overall, these hypotheses are based on niche and neutral theory, accounting for the relative roles of environmental and spatial processes (or a combination of them) in shaping metacommunities. Recent studies have addressed these issues on a variety of spatial and temporal scales, habitats and taxonomic groups. Moreover, life history and functional traits of species such as dispersal abilities and rarity have begun to be considered in studies of beta diversity. In this article we briefly review some of these new tools and approaches developed in recent years, and illustrate them by using case studies in aquatic ecosystems. Ecólogos geralmente estimam médias, mas dedicam pouca atenção à variação. O estudo da variação é um aspecto chave para entender sistemas naturais e fazer predições. Em ecologia de comunidades, a maioria dos estudos foca na diversidade local de espécies (diversidade alfa), e apenas recentemente ecólogos passaram a dar atenção apropriada a variação na composição de comunidades entre sítios amostrais (diversidade beta). Isto acontece apesar do fato das primeiras tentativas de estimar diversidade beta terem sido feitas pelos trabalhos pioneiros de Koch e Whittaker na década de 1950. Houve significativo progresso na última década no desenvolvimento tanto de métodos como de hipóteses sobre a origem e manutenção da variação na composição de comunidades. Por exemplo, métodos estão disponíveis para particionar a diversidade total de uma região (diversidade gama) num componente local (alfa) e diversos componentes de diversidade beta, cada um referente a uma escala na hierarquia. A popularização da chamada abordagem de dados brutos (raw-data approach) (baseada em técnicas de ordenação parcial restrita) e abordagem baseada em distância (distance-based approach) (baseada em correlações de matrizes de dissimilaridade/distância) tem possibilitado a avaliação de hipóteses sobre os padrões de diversidade beta. De maneira geral, estas hipóteses são baseadas nas teorias de nicho e neutra, e levam em consideração o papel do ambiente e do espaço (ou combinação deles) na determinação das metacomunidades. Estudos recentes avaliaram estes temas em grande variedade de escalas espaciais e temporais, de habitats e grupos taxonômicos. Adicionalmente, histórias de vida e traços funcionais das espécies tais como habilidades de dispersão e raridade estão começando a ser consideradas nos estudos de diversidade beta. Neste artigo nós revisamos brevemente algumas destas novas ferramentas e abordagens e as ilustramos com estudos de caso em ecossistemas aquáticos.